Minimum inhibitory concentrations of amphotericin B against Candida krusei isolates from a French teaching hospital laboratory: a retrospective study over 8 years. Issue 1 (23rd April 2012) - Murat, Jean‐Benjamin; Lebeau, Bernadette; Chumpitazi, Bernabé; Cornet, Muriel; Maubon, Danièle; Faure, Odile; Quesada, Jean‐Louis; Thiebaut‐Bertrand, Anne; Timsit, Jean‐François; Pelloux, Hervé
Summary Recent studies have shown decreased susceptibility of Candida krusei to amphotericin B (AmB), in addition to its inherent resistance to fluconazole. The susceptibility of C. krusei to AmB was studied in the Parasitology–Mycology laboratory of Grenoble Teaching Hospital, France. Between 2003 and 2011, we analysed 200 C. krusei isolates from 130 patients. The isolates were mainly collected in intensive care, cardio‐thoracic and cancer/haematology units. Minimum inhibitory concentrations (MICs) were determined by the E‐test method. The modal MIC was 0.5 μg ml−1; the MIC50 and MIC90 (MICs encompassing 50% and 90% of all isolates tested, respectively) were 0.5 μg ml−1 and 1 μg ml−1. The Cuzick's and Kendall's tests showed a significant increase in MIC values between 2003 and 2011 (P = 0.001 and P ≤ 0.001, respectively), regardless of age or gender. No statistical difference was reached with these tests when the first 100 or 50 data were excluded. Despite the increase observed in the first period of the study, our results confirm the low AmB MICs reported in previous studies. However, some authors have recently reported much higher MICs. This discrepancy cannot be explained by method biases and could reflect C. krusei epidemiological differences among populations.